2018
DOI: 10.18240/ijo.2018.07.18
|View full text |Cite
|
Sign up to set email alerts
|

Macular integrity assessment to determine the association between macular microstructure and functional parameters in diabetic macular edema

Abstract: Functional (BCVA and visual field) and morphological parameters (retinal thickness) were significantly associated with an intact IS/OS. Local photoreceptor integrity was a strong predictor of local visual function throughout the retina. MI revealed the functional status in DME, reflecting the IS/OS juction status in the macula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A series of past studies has shown that changes in the retinal or its sublayer's thickness in diseased eyes were associated with visual acuity and function 9-14 , and macular thickness has thus been proposed as a potential surrogate for visual function. Previous studies also reported poorer vision in cases who presented with signs of disrupted retinal layers such as the retinal inner layers, external limiting membrane or the ellipsoid zone [15][16][17] . The association between macular thickness and self-reported visual functioning has only been evaluated in diseased eyes such as age-related macular degeneration 18 .…”
Section: Optical Coherence Tomography (Oct) Is a Non-invasive Imaging...mentioning
confidence: 87%
“…A series of past studies has shown that changes in the retinal or its sublayer's thickness in diseased eyes were associated with visual acuity and function 9-14 , and macular thickness has thus been proposed as a potential surrogate for visual function. Previous studies also reported poorer vision in cases who presented with signs of disrupted retinal layers such as the retinal inner layers, external limiting membrane or the ellipsoid zone [15][16][17] . The association between macular thickness and self-reported visual functioning has only been evaluated in diseased eyes such as age-related macular degeneration 18 .…”
Section: Optical Coherence Tomography (Oct) Is a Non-invasive Imaging...mentioning
confidence: 87%
“…Larger extents of 3 mm have also been examined 30 ; however, we chose to review the central 1 mm of the foveal region, because this is where outer retinal disruptions in retinal disease are typically examined. 31 , 32 RPE sinuosity was significantly greater for the central 1 mm vs. the entire B-scan length in AMD groups ( P = 0.04) ( Fig. 2 A), but diagnostic accuracy was unaffected (1 mm aROC, 0.917; entire scan aROC, 0.893) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have found correlation between EZ disruption and significant reduction of macular sensitivity in DMO eyes. Wang et al have reported the macular integrity index (MI) as a useful benchmark of reflecting functional status in DMO [ 52 ]. MI denotes the percentage of threshold drop to measure local functional deterioration, and has been found to be significantly and independently correlated with EZ disruption.…”
Section: Objective Factorsmentioning
confidence: 99%